Penanganan Tindak Kekerasan Dalam Rumah Tangga di Kelurahan Bonto Perak Kecamatan Pangkajene Kabupaten PANGKEP - Hambali H Husaini; St Harlina; Habiba; Djunarti; Haryati Wagiman; Fahrisal Husain (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
Divorce cases in Pangkep Regency are caused by disputes between husband and wife that occur continuously so that they feel that there is no longer a match for each other. "According to the data, there have been 16 types of continuous dispute cases that have occurred. (KDRT) is a lot, domestic violence is a violation of human rights and crime against humanity as well as a form of discrimination that must be abolished. So that Law No. 23/2004 is expected to provide guarantees in preventing domestic violence, taking action against perpetrators, and protecting victims, the purpose of PKM (Community Service) ADPERTISI in Pangkep Regency the form of activities carried out can provide an understanding of the handling of acts of domestic violence with the presentation method and discussion between the ADPERTISI team and the community in Bonto Perak Village, Pangkajene District, Pangkep Regency.